The Effect of Transformational Leadership and Transactional Leadership on Innovative Work Behavior with Knowledge Sharing as Mediation - Muhammad Fathur Rozaq; Ida Maftukhah (Universitas Negeri Semarang, 2024)
This study aims to examine the effect of transformational leadership and transactional leadership on innovative work behavior with knowledge sharing as a mediator. The method used in this research is quantitative method, respondents 81 people in Mitra Swalayan Purwodadi employees. The sampling technique uses saturated samples with data collection techniques using questionnaires to respondents. The data in the study were analyzed using the Structural Equation Model (SEM) technique with SmartPLS. The test results in this study show that the direct effect of transformational leadership and transactional leadership on innovative work behavior is not significant. While the direct effect of transformational leadership and transactional leadership on knowledge sharing is significant, besides the effect of knowledge sharing on innovative work behavior is significant. Furthermore, this study found a significant influence between transformational leadership and transactional leadership on innovative work behavior mediated knowledge sharing.